Impact of Emotional-Volitional Sphere of Future Specialists of Risky Professions on Professional Training Performance (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Objective: The professional activities of specialists of risky professions are carried out in extreme conditions, characterized by a significant number of stressful factors, which, if the professional qualities of specialists are not sufficiently developed, leads to a decrease in the efficiency of performance of official duties, professional burnout, and psychosomatic disorders.Background: The success of the performance of service tasks is primarily influenced by the developmental level of the emotional-volitional sphere, in particular self-regulation, emotional-volitional stability, ensuring the ability to make autonomous decisions, form and determine tasks following the requirements of complex, changing situations, and therefore, achieve their goals. The article aims to analyze the emotional and volitional state of future specialists of risky professions during training.Method: The leading research method was observation. The emotional-volitional sphere is an integral part of the system of regulating activity as a professional. During the research, the main areas of the formation of the emotional-volitional sphere were identified. With the help of psychological analysis, the important properties of future specialists in the development of the emotional-volitional sphere have been determined.Results: The analysis results show that future specialists have an average and low level of stylistic possibilities for self-regulation (modeling, programming, autonomy). The reasons for the low progress of future specialists have been determined.Conclusion: The practical significance of the research lies in the development of recommendations for training and the formation of the emotional-volitional sphere during educational activities.